Antimicrobial synergy between carprofen and doxycycline against methicillin-resistant Staphylococcus pseudintermedius ST71. Issue 1 (December 2016) - Brochmann, Rikke; Helmfrid, Alexandra; Jana, Bimal; Magnowska, Zofia; Guardabassi, Luca
Abstract Background New therapeutic strategies are needed to face the rapid spread of multidrug-resistant staphylococci in veterinary medicine. The objective of this study was to identify synergies between antimicrobial and non-antimicrobial drugs commonly used in companion animals as a possible strategy to restore antimicrobial susceptibility in methicillin-resistantStaphylococcus pseudintermedius (MRSP). Results A total of 216 antimicrobial/non-antimicrobial drug combinations were screened by disk diffusion using a clinical MRSP sequence type (ST) 71 strain resistant to all six antimicrobials tested (ampicillin, ciprofloxacin, clindamycin, doxycycline, oxacillin and trimethoprim/sulfamethoxazole). The most promising drug combination (doxycycline-carprofen) was further assessed by checkerboard testing extended to four additional MRSP strains belonging to ST71 or ST68, and by growth inhibition experiments. Seven non-antimicrobial drugs (bromhexine, acepromazine, amitriptyline, clomipramine, carprofen, fluoxetine and ketoconazole) displayed minimum inhibitory concentrations (MICs) ranging between 32 and >4096 mg/L, and enhanced antimicrobial activity of one or more antimicrobials. Secondary screening by checkerboard assay revealed a synergistic antimicrobial effect between carprofen and doxycycline, with the sum of the fractional inhibitory concentration indexes (ΣFICI) ranging between 0.3 and 0.5 depending on drug concentration. Checkerboard testing of multiple MRSP strains revealed a clear association between synergy and carriage oftetK, which is a typical feature of MRSP ST71. An increased growth inhibition was observed when MRSP ST71 cells in exponential phase were exposed to 0.5/32 mg/L of doxycycline/carprofen compared to individual drug exposure. Conclusions Carprofen restores in vitro susceptibility to doxycycline inS. pseudintermedius strains carryingtetK such as MRSP ST71. Further research is warranted to elucidate the molecular mechanism behind the identified synergy and its linkage totetK .